REALISTIC MATHEMATICS EDUCATION AND ETHNOMATHEMATICS WORKSHEETS: A COMPARATIVE EFFECTIVENESS STUDY - Anshori, Muhamad Irfan; Inayati, Syarifah; Chasanah, Alifatul; Ridho, Mohammad Rosyid; Abu Jaya, Risal (Universitas Tanjungpura, 2026)
Low quantitative literacy and mathematical problem-solving skills among Indonesian students are the background for this study. This study aims to compare the effectiveness of using worksheets based on Realistic Mathematics Education (RME) and worksheets based on Ethnomathematics in improving the quantitative literacy and mathematical problem-solving skills of high school students in spatial geometry. This study used a quantitative experimental method with a posttest control group design involving two treatment groups. The research sample consisted of 100 high school students divided into two treatment groups, one group using RME-based worksheets and one group using ethnomathematics-based worksheets. The research instruments were quantitative literacy tests and mathematical problem-solving ability tests on spatial geometry material. The results showed that students who learned using RME-based worksheets obtained significantly higher quantitative literacy and mathematical problem-solving ability scores than students who learned using ethnomathematics-based worksheets. MANOVA analysis followed by univariate ANOVA confirmed significant differences in both variables. In conclusion, RME-based worksheets are more effective than ethnomathematics-based worksheets in improving quantitative literacy and mathematical problem-solving skills in spatial geometry.